USING COMIC STRIPS TO IMPROVE THE ABILITY OF THE SECOND YEAR STUDENTS OF SMA NEGERI 5 PEKANBARU IN WRITING NARRATIVE TEXTS - Dedel Surya; Atni Prawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis paper was aimed at finding out to what extent comic strips can improve the ability of the second year students of SMA Negeri 5 Pekanbaru in writing narrative texts. The participants of this research were 36 students of the second year students of SMA Negeri 5 Pekanbaru. This research was conducted in 2 cycles. The data collection technique were obtained through (1)observation sheet which was applied to know the students’ activities during teaching and learning process, (2) test was done to measures students’ achievement, and (3) field note was done to obtain information about teacher, the students’ activities and performance during the implementation of comic strips. The research findings can be briefly explained as follows; firstly, the students’ ability in writing narrative texts could be improved by using comic strips. Before the research was done, the mean score of students’ pre-test was 60.4. After the research has done for cycle 1, the mean score of students’ writing was 68.1. In post test 2 mean score of students’ writing increased up to 78.4. Secondly, the students’ activeness increased from cycle 1 to cycle 2. Finally, the students enjoyed to write narrative text and develop their writing.Keyword : Comic Strips, Writing, Narrative Text